2003
DOI: 10.1034/j.1600-0455.2003.00098.x
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Stereotactic Fine Needle Aspiration Cytology and Core Needle Biopsy in 522 Non-Palpable Breast Lesions

Abstract: S-CNB was more accurate than S-FNAC in the diagnosis of non-palpable breast cancer.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
24
0
2

Year Published

2004
2004
2010
2010

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 47 publications
(28 citation statements)
references
References 21 publications
2
24
0
2
Order By: Relevance
“…Direct comparison of the results of various FNAC studies may not be appropriate, as the defining conditions of various diagnostic categories, technical details, and other parameters may not be the same [3]. Results from studies comparing CNB and FNAC showed generally a higher sensitivity and specificity for CNB than FNAC, with a sensitivity and specificity for malignancy of more than 90% for CNB, whereas for FNAC, the corresponding figures had been reported to be lower than 70% [11], and in one series, a sensitivity of 34.5% and specificity of 47.6% were reported [13]. When only the definitive benign and malignant categories were considered (i.e., ignoring the atypical and suspicious categories), the performance indices of FNAC improved and reached above 95% [15].…”
Section: Non Palpable Mammographic Detected Lesionsmentioning
confidence: 85%
See 4 more Smart Citations
“…Direct comparison of the results of various FNAC studies may not be appropriate, as the defining conditions of various diagnostic categories, technical details, and other parameters may not be the same [3]. Results from studies comparing CNB and FNAC showed generally a higher sensitivity and specificity for CNB than FNAC, with a sensitivity and specificity for malignancy of more than 90% for CNB, whereas for FNAC, the corresponding figures had been reported to be lower than 70% [11], and in one series, a sensitivity of 34.5% and specificity of 47.6% were reported [13]. When only the definitive benign and malignant categories were considered (i.e., ignoring the atypical and suspicious categories), the performance indices of FNAC improved and reached above 95% [15].…”
Section: Non Palpable Mammographic Detected Lesionsmentioning
confidence: 85%
“…This had been aptly illustrated in a study in which the inadequacy rate was higher in benign than malignant lesions upon final excision [12]. The inadequacy rate of CNB in non palpable lesions ranged from 0 to 20% [11,13,17]. Although this range appeared to be significantly lower than that for FNAC, one has to interpret this with caution.…”
Section: Non Palpable Mammographic Detected Lesionsmentioning
confidence: 85%
See 3 more Smart Citations